TASK AVERSIVENESS, FEAR OF FAILURE DAN PROKRASTINASI AKADEMIK PADA MAHASISWA - Elfriska Auly Adenia; Dewi Mustami’ah; Lutfi Arya (Jurnal Psikologi Poseidon, 2021)
This study aimed to determine the effect of task aversiveness and fear of failure on academic procrastination in students of the Faculty of Psychology at Hang Tuah University. There were 202 participan in the study. The sampling technique used quota sampling. Analysis of hypothesis testing using multiple linear regression. This study uses a scale of task aversiveness, fear of failure and academic procrastination. The results showed that there was a significant effect of task aversiveness and fear of failure on academic procrastination with an R Square value of 0.148. Other results show that the correlation coefficient of task aversiveness on academic procrastination is 11.1% and fear of failure on academic procrastination is 13.6%.